2003
DOI: 10.1002/ejoc.200390152
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Stepwise Release of Fragrance Alcohols from Dendrimer‐Based 2‐Carbamoylbenzoates by Neighbouring Group Participation

Abstract: Keywords: Dendrimers / Fragrances / Neighboring-group effects / Kinetics / Delivery systems / Controlled release 2-Carbamoylbenzoates which are chemically bound to the surface of dendrimers were found to release tertiary fragrance alcohols by neighbouring group assisted alkaline hydrolysis under mild reaction conditions. Owing to the excellent separation of the intermediate reaction products by analytical HPLC, the kinetic rate constants of the first two consecutive reaction steps of fragrance release could be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…[140,141] The excellent separation of the parent dendrimer 66 from its monocyclized intermediate by HPLC allowed the determination of the rate constants for the first two cyclization steps. [141] It was shown that the release kinetics are not influenced by steric effects and are thus independent of the dendrimer size. The fact that no enzymes or other bulky reagents are needed to release the active substances from the dendrimer surface allows the preparation of large molecules Scheme 21.…”
Section: Carboxylatesmentioning
confidence: 99%
“…[140,141] The excellent separation of the parent dendrimer 66 from its monocyclized intermediate by HPLC allowed the determination of the rate constants for the first two cyclization steps. [141] It was shown that the release kinetics are not influenced by steric effects and are thus independent of the dendrimer size. The fact that no enzymes or other bulky reagents are needed to release the active substances from the dendrimer surface allows the preparation of large molecules Scheme 21.…”
Section: Carboxylatesmentioning
confidence: 99%
“…[8,9] Since, for steric reasons, a larger number of molecules can be attached to the dendrimer surface than could possibly be physically trapped within the dendritic branches, the release of bioactive compounds by covalentbond cleavage from the dendrimer surface is particularly interesting for high-generation dendrimers. Redox reactions, [10][11][12] photofragmentations, [13][14][15] hydrolyses [16][17][18][19] and the action of enzymes or catalytic antibodies [20][21][22][23] were identified as the most common triggers for covalent-bond cleavage at the dendrimer surface. Besides drug delivery, this concept was also successfully used to control the release of fragrances.…”
Section: Introductionmentioning
confidence: 99%
“…Besides drug delivery, this concept was also successfully used to control the release of fragrances. [18,23,24] Water is the most important solvent for all types of biological applications, and the release of the active compound must therefore proceed in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations